2020
DOI: 10.1016/j.jcv.2020.104380
|View full text |Cite
|
Sign up to set email alerts
|

Supportive Treatment with Tocilizumab for COVID-19: A Systematic Review

Abstract: Highlights• Emerging data shows a correlation between serum IL-6 and COVID-19 infection severity.• Tocilizumab, an IL-6 inhibitor, is a potential supportive treatment for COVID-19.• Preliminary investigations are showing benefits with tocilizumab for COVID-19.• Ongoing RCTs will clarify tocilizumab's place in therapy for COVID-19.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
122
0
10

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 14 publications
2
122
0
10
Order By: Relevance
“…Experimental therapies have been used since the outbreak of the COVID-19 pandemic and expert societies guided to enroll patients in clinical studies when possible, as no standard treatment exists so far. Although other drugs have been tested, the only potential supportive treatment for COVID-19 appears to be an IL-6 inhibitor, tocilizumab (17).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental therapies have been used since the outbreak of the COVID-19 pandemic and expert societies guided to enroll patients in clinical studies when possible, as no standard treatment exists so far. Although other drugs have been tested, the only potential supportive treatment for COVID-19 appears to be an IL-6 inhibitor, tocilizumab (17).…”
Section: Discussionmentioning
confidence: 99%
“…Most of them focused on a certain specific subfields of COVID-19 research, such as drug therapy, diagnostic methods, or clinical symptoms. For example, Alzghari et al [ 2 ] performed a systematic review to investigate the effect of Tocilizumab on COVID-19, and Zhu et al [ 3 ] systematically reviewed the CT imaging features of COVID-19 to provide reference for clinical practice. The second kind is the bibliometric analysis which uses quantitative analysis methods to describe literature in a particular research domain.…”
Section: Introductionmentioning
confidence: 99%
“…[8]. Limited observational studies have demonstrated tocilizumab to be associated with improvements in in ammatory markers, clinical response, and survival [9][10][11][12][13][14][15][16]. During an unprecedented time when proven effective therapies remain lacking, we aimed to describe our experience using off-label tocilizumab for COVID-19.…”
Section: Introductionmentioning
confidence: 99%